Hope after Harm: Rajāʾ, Everyday Religion, and Post-Traumatic Growth among Women Survivors of Dating Violence - Ratu Rania; Triyono Triyono; Meysella Hanim (UIN Sunan Kalijaga Yogyakarta, 2025)
Dating violence can have profound psychological effects. However, such traumatic experiences may also trigger post-traumatic growth (PTG) when individuals are able to find new meaning in their lives. This study examines the role of rajāʾ as a religious coping mechanism that facilitates PTG in survivors of dating violence. Employing a qualitative case study approach, data were collected through in-depth interviews. The analysis utilized time-series analysis, pattern matching, and explanation building. The results revealed that the recovery process occurred in two phases: the disorientation phase, characterized by emotional distress, and the meaning reconstruction phase, during which traumatic experiences were reinterpreted within a spiritual framework. Positive changes were observed across five dimensions of PTG: relationships with others, personal strength, new life possibilities, appreciation of life, and spiritual change. Within the ambivalent texture of everyday religious life, where romantic relationships outside of marriage may be seen as potentially compromising ideals of religious piety, this study argues that rajāʾ functions not only as theological hope but also as an experiential orientation that helps survivors regulate emotions, reconstruct meaning, and transform suffering into a catalyst for resilience and spiritual growth.